Tolerating Partial Failures on IEC 61499 Applications - Mário de Sousa (2015)
In a modern industrial environment control programs are distributed among several devices. This raises new challenges, especially in handling the failure modes. Automatic reconfiguration is a possible approach in dealing with partial failures. The authors have proposed an IEC 61499 based replication framework for building fault tolerant applications - thus a failure of one sub-component does not to jeopardize the execution of the whole application. The proposed framework is capable of supporting dynamic reconfiguration on all automation levels in an industrial cell in order to patronage a fault tolerant and seamless production line.